FORMULASI DAN TINGKAT KESUKAAN KONSUMEN PADA MINUMAN SERBUK INSTAN DARI TANAMAN EMPON-EMPON DENGAN KOMPOSISI JAHE, TEMULAWAK, KUNYIT DAN SEREH - Husnani Husnani; Syarifah Nadia H (Jurnal Komunitas Farmasi Nasional, 2021)
Instant powder drink is a preparation made from plants which is processed into powder form, and ready to use by mixing it with warm water. The empon-empon plant has been widely used traditionally to treat various diseases, especially it is useful to increase body immunity, but it is not liked by the public because of its complicated use and unpleasant taste and aroma, therefore it needs to be made in practical dosage forms and good for consumption. and can be stored for a long time as a healthy instant dry form. This study aims to determine the best formula seen from the physical quality of the preparation and the formula that consumers like. This research was conducted experimentally using variations in the addition of granulated sugar to each formula. The parameters observed included yield, solubility time, pH, water content and organoleptic tests covering color, aroma and taste (hedonic scale).